2019
DOI: 10.1038/s41374-019-0259-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic signature of lymphangiogenesis during acute kidney injury and chronic kidney disease

Abstract: Acute kidney injury (AKI) and chronic kidney disease (CKD) are interconnected syndromes with significant attributable morbidity and mortality. The disturbing trend of increasing incidence and prevalence of these clinical conditions highlights the urgent need for better understanding of the underlying mechanisms that are involved in pathogenesis of these conditions. Lymphangiogenesis and its involvement in various inflammatory conditions is increasingly recognized while its role in AKI and CKD remains to be ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 47 publications
2
54
0
Order By: Relevance
“…In addition, VEGF-D is another major promoter of lymphangiogenesis, also depending on VEGFR-3, but its ability to promote lymphangiogenesis is less important than that of VEGF-C. The injury tubules produce a large amount of VEGF-C and VEGF-D during acute kidney injury and chronic kidney disease [49]. Kinashi et al [50] found that connective tissue growth factor (CTGF) is another important determinant of lymphangiogenesis.…”
Section: Lymphangiogenesis and Kidney Diseasementioning
confidence: 99%
“…In addition, VEGF-D is another major promoter of lymphangiogenesis, also depending on VEGFR-3, but its ability to promote lymphangiogenesis is less important than that of VEGF-C. The injury tubules produce a large amount of VEGF-C and VEGF-D during acute kidney injury and chronic kidney disease [49]. Kinashi et al [50] found that connective tissue growth factor (CTGF) is another important determinant of lymphangiogenesis.…”
Section: Lymphangiogenesis and Kidney Diseasementioning
confidence: 99%
“…Renal lymphangiogenesis has been reported to occur in many different clinical scenarios, including cisplatin-induced kidney disease, amongst others (4, 5, 38, 46, 47), and it has generated a logical enthusiasm for targeting the lymphatic system in a wide spectrum of kidney diseases (6, 36, 37, 48). Cisplatin injury did not lead to differences in renal outcomes in Vegfr3 Chy /+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas peritubular capillaries undergo rarefaction, potentially triggering interstitial hypoxia and generating a profibrogenic environment within diseased kidney 59 , renal lymphatics proliferate and sprout, giving rise to new vessels in a process termed lymphangiogenesis 60 . In biopsies of immunoglobulin A nephropathy, focal glomerulosclerosis, lupus, anti-neutrophil cytoplasmic antibody-related glomerulonephritis, diabetic kidney disease (DKD) and chronic interstitial nephritis acquired from patients ranging from moderate CKD to end-stage kidney disease (ESKD), the cross sectional area of lymphatics is significantly greater than in non-diseased kidneys 26,61 ; a finding replicated in multiple murine models of CKD 54,[62][63][64][65][66] .…”
Section: Lymphangiogenesis and Its Role In Chronic Renal Injury And Fmentioning
confidence: 93%
“…However, several questions remain. Structural changes to renal lymphatics are not evident in murine or human AKI 26,66 . However, the possibility that renal lymphatics are altered at the molecular or functional level in acute nephropathy, and whether these can be exploited to prevent the transition from AKI to CKD, warrants further study.…”
Section: Future Directionsmentioning
confidence: 93%